The Moderating Effect of Social Support on the Relationship Between Grit and Employee Well-being in Indonesia - Sulistyowati, Mike; Maulana, Herdiyan; Armeini Rangkuti, Anna (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2025)
Well-being has become a critical concern in the VUCA (volatility, uncertainty, complexity, ambiguity) environment, as it directly affects organizational sustainability, individual adaptability, and overall productivity. Personal resources such as grit and external resources like social support play essential roles in sustaining well-being under these challenging conditions. This research aims to investigate the role of social support as a moderator in the relationship between grit and employee well-being in Indonesia. The proposed hypotheses are that grit positively affects well-being and that social support moderates this effect. The respondents consist of 507 employees, with 55 respondents used for validity and reliability testing. The sample was selected using purposive sampling techniques. Instruments used included the Indonesian Well-being Scale, Employee Grit Scale, and Multidimensional Scale of Perceived Social Support (Indonesian adaptation). Data analysis was conducted using moderation regression with Hayes Model 1 (Hayes, 2017). The results show that grit positively affects well-being, where employees with high grit experience better well-being (β = 0.42, p < 0.01). Social support has a significant direct effect on well-being (β = 0.35, p < 0.05), indicating that social support positively contributes to employee well-being. However, the moderating effect of social support on the influence of grit on well-being was not significant (β = 0.08, p > 0.05), suggesting that social support does not always strengthen the effect of grit on well-being. A unique finding of this research is social support ambivalence, particularly within Indonesia’s collectivist culture. On the one hand, social support enhances well-being, yet on the other hand, it creates excessive social responsibility (social pressure), which potentially reduces employee well-being. The implications of this study provide recommendations for organizations to design grit development strategies focusing on employee perseverance and to implement a balanced social support system to enhance employee performance and well-being.